Russian -Ukrainian relationsand its impact on NATO - BOUHMAMA, Oussama (Journal of Human Sciences, 2015)
The heritage of the Soviets continues to be reflected in Russian policy-making ever since the collapse of the Soviet Union. Ukraine decided to be part of the west while seeking to join the European Union and NATO at the same time as the Russian authorities decided to regain Russia’s international status. When Putin came to power, he was pursuing the expansion of Russian influence over post-Soviet space. Russia raised the idea of the multi-polar world and condemned the prevailing dominance of one country. Putin declared that Russia is going to take its role in a multi-polar international system. In order to create a balance of power, Russia had to create its sphere of influence, Moscow identified the post-Soviet space as its sphere of vital interests, and thus Russian backyard became the first priority in Russian Foreign Policy. Ukraine appeared at the forefront of the political tension between the West and Russia.